2003
DOI: 10.1161/01.hyp.0000072772.74183.5f
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Redistribution of Focal Adhesion Kinase and Its Related Nonkinase in Hypertrophic Myocardium

Abstract: Abstract-Focal adhesion kinase (FAK) and focal adhesion kinase-related nonkinase (FRNK) are likely involved in mechanical signaling during hypertension. We investigated expression, subcellular distribution, and phosphorylation of FAK, as well as FRNK in left ventricles of spontaneously hypertensive heart failure rats. Key Words: hypertrophy Ⅲ heart failure Ⅲ kinase Ⅲ cell signaling O ur studies on lean female spontaneously hypertensive heart failure (SHHF) rats 1 have shown that myocyte cross-sectional growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
6

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 22 publications
(24 reference statements)
2
42
0
6
Order By: Relevance
“…However, the presence of truncated forms of FAK and of the full-length protein in the nucleus has already been reported, suggesting that FAK may have a role in the nucleus under some circumstances (55,56). An attractive hypothesis would thus be that FAK undergoes a nucleocytoplasmic cycling that allows its nuclear sumoylation in the presence of PIAS1.…”
Section: Sumoylated Fak Is Enriched In the Nuclear Fraction And Sumoymentioning
confidence: 97%
“…However, the presence of truncated forms of FAK and of the full-length protein in the nucleus has already been reported, suggesting that FAK may have a role in the nucleus under some circumstances (55,56). An attractive hypothesis would thus be that FAK undergoes a nucleocytoplasmic cycling that allows its nuclear sumoylation in the presence of PIAS1.…”
Section: Sumoylated Fak Is Enriched In the Nuclear Fraction And Sumoymentioning
confidence: 97%
“…Additional studies revealed that full-length FAK and Pyk2 could localize to the nucleus under appropriate conditions and in a number of different cell types (Aoto et al, 2002;Yi et al, 2003). Recent evidence has shed some light on the mechanisms regulating nuclear localization and nuclear function.…”
Section: Fak Functions In the Nucleusmentioning
confidence: 99%
“…1). However, both full-length FAK and the C-terminal domain of FAK can be localized to the nucleus in cardiomyocytes (Yi et al, 2003). This implies an alternative mechanism because the C-terminal domain lacks the N-terminal nuclear localization sequences, but a potential mechanism has not been defined.…”
Section: Fak Functions In the Nucleusmentioning
confidence: 99%
“…LV tissues from 5 mice in each group were homogenized using a PT1200C Polytron Homogenizer in ice-cold Tris/Triton extraction buffer (10mM Tris-HCl, 50mM NaCl, 5mM EGTA, 1%Triton X-100, pH 7.4) with phosphatase inhibitors (0.1mM Na 3 VO 4 , 30mM Na 4 P 2 O 7 , 50mM NaF) and proteinase inhibitors (10mg/ml PMSF, 1μg/ml aprotinin) [16]. The homogenates were centrifuged at 15,000 g for 15 minutes and separated into Triton soluble supernatant and insoluble pellet.…”
Section: Protein Separation and Western Blot Analysesmentioning
confidence: 99%